ENGLISH STUDENTS’ PROBLEMS IN WRITING THESIS PROPOSAL AT MUHAMMADIYAH UNIVERESITY OF BENGKULU - Sinarman Jaya; Bella Permata Ayu (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research aimed to find out what are the problems faced by English students in writing a thesis proposal and how do English students solve the problems in writing a thesis proposal. This research used a qualitative descriptive method. The subjects of this research were 8th semester students of English Study Program of Muhammadiyah University of Bengkulu in Academic Year 2022. 25 English students who had written their thesis proposal participated in this study. Researcher used interviews as a data collection technique. The results of this study showed that students experienced 4 general problems in writing thesis proposals. Namely: academic problems, writing problems, communication problems with supervisors and personal problems. The ways for students to solve the problems are by way of guidance with supervisors, browsing on the internet, reading more references, motivating them selves to write, and making a schedule so that writing is still done regularly.what are the problems. The conclusion of this study are English Students at Muhammadiyah University of Bengkulu faced 4 types of problems in writing thesis proposal. Academic problems, writing problems. communication problems, and personal problems. And they had the different ways to solved the problems. Key Words: Problem, Writing, Thesis Proposal